A review of searcher efficiency and carcass persistence in infrastructure-driven mortality assessment studies. (June 2018) - Barrientos, Rafael; Martins, Ricardo C.; Ascensão, Fernando; D'Amico, Marcello; Moreira, Francisco; Borda-de-Água, Luís
Abstract: Infrastructures in natural areas are expanding rapidly worldwide. Consequently, roads, power-lines, and wind-farms cause millions of fatalities across several animal groups. Assessing the population impact of these infrastructures requires sound estimates of the total number of fatalities. These estimates can be heavily biased due to differences in searcher efficiency and carcass persistence rates, which may ultimately lead to the incorrect quantification of actual mortality, or to the inadequate prioritization of locations for mitigation. We reviewed 294 studies using carcass surveys conducted worldwide and performed analyses on the effects of variables potentially influencing searcher efficiency and carcass persistence rates. Our analytical review, including the largest number of studies to date, the use of multivariate approaches, and the study weighting by sample size, contradicts some previous findings. Whereas body mass is confirmed as the most important variable accounting for both biases, equally important was the use of dogs in searches, as they increased searcher efficiency for small carcasses, and the taxon of carcasses for persistence, as mammals persisted at higher rates than birds and the latter at higher rates than amphibians. Our results provide little support for previous ideas on the influence of the use of domestic or thawed carcasses on persistence rates. Our findings contribute to synthesizing knowledge on the main factors affecting the two main mortality biases across carcass field experiments, and suggest recommendations for improving survey designs in future studies to minimize the biases identified. Highlights: Human infrastructures represent a huge source of wildlife mortality. To estimate the impact on population viability we need to know the actual mortality. Carcass body mass and the use of dogs determined searcher efficiency rate. Carcass body mass and taxon determined carcass persistence rate. The use of domestic or thawed carcasses did not affect persistence rates.